EFFECTIVENESS OF GUIDED IMAGERY AND VIRTUAL REALITY ON PSYCHOLOGICAL COMFORT IN HEMODIALYSIS PATIENTS: A SYSTEMATIC REVIEW - Nurtati Anggraeni; Eko Winarto; M. Jamaluddin; Sabina Gero (Nursing Sciences Journal, 2026)
Background: Hemodialysis patients often experience anxiety, stress, depression, and pain due to invasive and repetitive procedures, resulting in reduced psychological comfort and quality of life. Guided imagery and virtual reality are non-pharmacological interventions that have the potential to reduce psychological distress during therapy. This study aims to evaluate the effectiveness of the two interventions through systematic review. Methods: A systematic search was conducted in PubMed, Scopus, Science Direct, and Google Scholar for studies published between 2018 and 2025. Study selection followed PRISMA guidelines, and data were synthesized using a narrative approach. A total of 198 records were identified, and 10 studies met the inclusion criteria. The PICO framework includes Population = patients’ hemodialysis; Intervention = guided imagery and/or virtual reality; Comparison = standard care or pre-intervention conditions; and Outcome = psychological comfort which includes anxiety, stress, depression, pain, sleep quality, and psychological well-being. Article searches were carried out systematically through PubMed, Scopus, and Google Scholar databases using keywords relevant to guided imagery, virtual reality, hemodialysis, and psychological outcomes. Results: A total of 10 studies met the inclusion criteria, with the study design dominated by randomized controlled trials (RCTs). The study came from Iran, Indonesia, Egypt, Australia, Spain, and Poland. The results showed that guided imagery- virtual reality significantly reduced anxiety, stress, depression, and pain perception compared to standard treatments or pre-intervention conditions. Some studies have also reported improvements in sleep quality, patient satisfaction, and psychological well-being during hemodialysis.Conclusion: Guided imagery and virtual reality are effective in reducing anxiety, stress, depression, and pain, as well as improving sleep quality and psychological well-being in hemodialysis patients.